Organizational Evolution, Learning, and Selection: A Genetic-Algorithm-Based Model - Bruderer, Erhard; Singh, Jitendra V. (Academy of Management Journal, 1996)
This study proposes a relatively simple computational model of organizational evolution based on the genetic algorithm. The model includes three organizational processes: variation, adaptation, and selection of routines. We use the model to demonstrate theoretically that environmental selection influences adaptation and adaptation, in turn, influences the selection process in a Darwinian model of evolution. Results of computer simulations are consistent with empirical observations, including the existence of three distinct phases of organizational evolution and the emergence of a dominant organizational design.